40 YEARS OF IGF1: Anti-insulin-like growth factor therapy in breast cancer. (July 2018) - Yee, Douglas
Abstract : Early preclinical and population data suggested a role for the type I insulin-like growth factor receptor (IGF1R) in the regulation of breast cancer growth and survival. To target this pathway, multiple monoclonal antibodies and tyrosine kinase inhibitors were developed and tested in clinical trials. While some of the early clinical trials suggested a benefit for these drugs, none of the attempts showed improved outcomes when compared to conventional therapy. This failure of the IGF1R inhibitors was pronounced in breast cancer; multiple trials testing IGF1R inhibition in estrogen receptor-positive breast cancer were conducted, none showed benefit. This review will evaluate the rationale for IGF1R inhibition, discuss results of the clinical trials and suggest a path forward.